110 Minima timings of ultra-short orbital period eclipsing binaries - Gazeas, K.; Loukaidou, G.; Tzouganatos, L.; Karampotsiou, E.; Petropoulou, M. (2017)
We present 110 times of minima of 7 ultra-short orbital period eclipsing binaries.
Keywords: CCD photometry